1996
DOI: 10.1103/physreve.54.5482
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties and shell analysis in random cellular structures

Abstract: We investigate the statistical properties of two-dimensional random cellular systems ͑froths͒ in terms of their shell structure. The froth is analyzed as a system of concentric layers of cells around a given central cell. We derive exact analytical relations for the topological properties of the sets of cells belonging to these layers. Experimental observations of the shell structure of two-dimensional soap froth are made and compared with the results on two kinds of Voronoi constructions. It is found that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
42
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 40 publications
4
42
1
Order By: Relevance
“…In soap froth we have shown certain universal features such as the generalized Aboav-Wearie law [16] for the average number M͑i, n͒ of edges of cells in the ith shell of the central cell with n sides. We also found that the number of cells K͑i, n͒ in the ith shell is linear in i with slope related to the Aboav parameter [17]. In this Letter, we study the generalized Aboav-Weaire law, which relates the correlation between the ith shell neighbors with the disorder of the i-shell perimeter.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…In soap froth we have shown certain universal features such as the generalized Aboav-Wearie law [16] for the average number M͑i, n͒ of edges of cells in the ith shell of the central cell with n sides. We also found that the number of cells K͑i, n͒ in the ith shell is linear in i with slope related to the Aboav parameter [17]. In this Letter, we study the generalized Aboav-Weaire law, which relates the correlation between the ith shell neighbors with the disorder of the i-shell perimeter.…”
mentioning
confidence: 89%
“…In this Letter, we study the generalized Aboav-Weaire law, which relates the correlation between the ith shell neighbors with the disorder of the i-shell perimeter. We find new universal features for shells beyond the first.Inspired by ideas from the renormalization group, we consider the generalization of the Aboav-Weaire law based on the shell model analysis [17,18]. We propose a generalized Aboav-Weaire law in the form…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our edge scaling hypothesis is simple and can be used to provide a phenomenological description of area scaling function, without going through the stochastic equation using von Neumann dynamics. However, we should remark here that any e v olution theory for froth without correlation e ects properly incorporated is not realistic, as experimental evidences for strong and long range correlation exist for real soap froth 12,13]. Our observation of edge scaling for individual topological class therefore poses new challenge for the theoretical understanding of evolving soap froth.…”
mentioning
confidence: 99%